Community-based interventions targeting multiple forms of malnutrition among adolescents in low-income and middle-income countries: protocol for a scoping review - Kurniawan, Adi Lukas; Ranisavljev, Marijana; Partap, Uttara; Shinde, Sachin; Ferrero, Elisabetta; Ostojic, Sergej; Mkwanazi, Ntombizodumo; Alangea, Deda Ogum; Neumann, Christine; Liu, Shuyan; Bärnighausen, Till; Fawzi, Wafaie W. (BMJ open, 2024)
Background Adolescent malnutrition is a significant public health challenge in low-income and middle-income countries (LMICs), with long-term consequences for health and development. Community-based interventions have the potential to address multiple forms of malnutrition and improve the health outcomes of adolescents. However, there is a limited understanding of the content, implementation and effectiveness of these interventions. This scoping review aims to synthesise evidence on community-based interventions targeting multiple forms of malnutrition among adolescents in LMICs and describe their effects on nutrition and health. - Methods and analysis A comprehensive search strategy will be implemented in multiple databases including MEDLINE (through PubMed), Embase, CENTRAL (through Cochrane Library) and grey literature, covering the period from 1 January 2000 to 14 July 2023. We will follow the Participants, Concept and Context model to design the search strategy. The inclusion criteria encompass randomised controlled trials and quasi-experimental studies focusing on adolescents aged 10-19 years. Various types of interventions, such as micronutrient supplementation, nutrition education, feeding interventions, physical activity and community environment interventions, will be considered. Two reviewers will perform data extraction independently, and, where relevant, risk of bias assessment will be conducted using standard Cochrane risk-of-bias tools. We will follow the PRISMA Extension for Scoping Reviews checklist while reporting results. - Ethics and dissemination The scope of this scoping review is restricted to publicly accessible databases that do not require prior ethical approval for access. The findings of this review will be shared through publications in peer-reviewed journals, and presentations at international and regional conferences and stakeholder meetings in LMICs. - Scoping review registration The final protocol was registered prospectively with the Open Science Framework on 19 July 2023 (https://osf.io/t2d78).